The Psychometric Properties of the Norwegian version of Child and Adolescent Psychiatric Assessment (CAPA) og Preschool Age Psychiatric Assessment (PAPA) - Jozefiak, Thomas; Berg-Nielsen, Turid Suzanne (PsykTestBarn, 2016)
Description: Child and Adolescent Psychiatric Assessment (CAPA) (2008), by Angold and colleagues) was translated into Norwegian by Jozefiak in 2010. Preschool Age Psychiatric Assessment (PAPA) (2004) was translated by Wichstrøm in 2006. Translations were conducted in collaboration with the original authors. Copyrightholder is Adrian Angold, Duke University USA. CAPA and PAPA are «interviewer-based» structured psychiatric interviews for both research and clinical purposes, assessing debut, duration, frequency and degree of symptoms in diagnoses according to DSM-IV and functional impairment. CAPA is a direct interview of children and adolescents aged 9-18. PAPA is an interview for parents of preschool-aged children aged 2-5. There are comprehensive «glossaries» available, specifying symptom definitions and rules for coding. The CAPA-interview lasts approximately 1-3 hours, while the PAPA-interview is somewhat longer (1,5-4 hours). The length of both interviews depend on the amount of child mental health symptoms. Three years relevant university college education is required for interviewers and a two-week training course including certification, administered by associates at Duke University. CAPA and PAPA is available in electronic versions, coding is conducted electronically by the interviewer during the interview, and diagnoses are set at Duke University using computer algorithms. Literature search: Nine Norwegian papers, but no Swedish/Danish papers, were included. The papers reported from two Norwegian studies with CAPA and PAPA. PAPA was used in a representative epidemiological study of a cohort consisting of preschoolers, aged 4 at baseline (N= 995) in Trondheim. CAPA was used in a high-risk population (N = 400) youth aged 12-20 who where in Residential Youth Care. Psychometrics: CAPA and PAPA showed good inter-rater reliability. Validity was documented by discriminative ability of clinical groups, association with known risk factors, prediction of outcome and satisfactory confirmatory factor analyses. Conclusion. Conclusion: We identified limited documentation for the psychometric properties of the Norwegian versions of the CAPA and PAPA interviews. Reliability and validity were satisfactory. The Norwegian versions are promising regarding future research, however, due to lack of studies from Scandinavian child mental health services it is not possible to give any recommendations for ordinary clinical use.